Galileo in Rome : the rise and fall of a troublesome genius - Shea, William R. (Oxford University Press, 2003)
A detailed, revisionist study of the life and career of the great Italian scientist offers a focused analysis of Galileo's relationship with the Catholic Church, discussing the theological furor caused by Galileo's Dialogue, the scientist's own role in the conflict, and the events of his trial by the Inquisition. (Biography).